Investigation into the Effects of Citric Acid on the Corrosion Behavior of AM 350 Stainless Steel Using Electrochemical Impedance Spectroscopy - Gaona Tiburcio, Citlalli; Villegas Tovar, José Miguel; Maldonado Bandala, Erick; Lara Banda, María del Refugio; Baltazar Zamora, Miguel Ángel; Méndez Ramírez, Ce Tochtli; Nieves Mendoza, Demetrio; Almaguer Cantú, Verónica; Jáquez Muñoz, Jesús Manuel; Landa Gómez, Aldo; Almeraya Calderón, Facundo (Molecular Diversity Preservation International, 2025)
Stainless steels are used in the aeronautical industry for their corrosion resistance and good mechanical performance. The chemical treatment used to improve corrosion resistance is passivation, forming a compact, continuous, adherent chromium oxide film. This research aimed to investigate the effect of citric acid at different concentrations (citric acid; citric acid + oxalic acid, citric acid + hydrogen peroxide, and citric acid + hydrogen peroxide + ethanol) on AM 350 stainless steel passivated for 90 and 120 min at 25 and 50 °C and immersed in 5% by weight sodium chloride (NaCl) solutions. The electrochemical technique used was electrochemical impedance spectroscopy (EIS) based on ASTM-G106. The EIS (equivalent circuit) results indicate that there are one and two constant phase elements (CPE), which indicate the presence of various factors on the stainless steel surface, such as roughness and the formation of porous and passive layers, respectively. A double-layer system was employed for some samples. However, when the ethanol was added to the passivation bath, the behavior changed to a one-time constant system. The AM 350 passivated in citric and oxalic acid presented the higher corrosion resistance with values of 6 × 105 Ω·cm2.